Bioinspired Interlocked and Hierarchical Design of ZnO Nanowire Arrays for Static and Dynamic Pressure‐Sensitive Electronic Skins. (7th April 2015) - Ha, Minjeong; Lim, Seongdong; Park, Jonghwa; Um, Doo‐Seung; Lee, Youngoh; Ko, Hyunhyub
Abstract : The development of electronic skin (e‐skin) is of great importance in human‐like robotics, healthcare, wearable electronics, and medical applications. In this paper, a bioinspired e‐skin design of hierarchical micro‐ and nano‐structured ZnO nanowire (NW) arrays in an interlocked geometry is suggested for the sensitive detection of both static and dynamic tactile stimuli through piezoresistive and piezoelectric transduction modes, respectively. The interlocked hierarchical structures enable a stress‐sensitive variation in the contact area between the interlocked ZnO NWs and also the efficient bending of ZnO NWs, which allow the sensitive detection of both static and dynamic tactile stimuli. The flexible e‐skin in a piezoresistive mode shows a high pressure sensitivity (−6.8 kPa −1 ) and an ultrafast response time (<5 ms), which enables the detection of minute static pressure (0.6 Pa), vibration level (0.1 m s −2 ), and sound pressure (≈57 dB). The flexible e‐skin in a piezoelectric mode is also demonstrated to be able to detect fast dynamic stimuli such as high frequency vibrations (≈250 Hz). The flexible e‐skins with both piezoresistive and piezoelectric sensing capabilities may find applications requiring both static and dynamic tactile perceptions such as robotic hands for dexterous manipulations and various healthcare monitoring devices. Abstract : Flexible electronic skins (e‐skins) with static and dynamic tactile sensing capabilities are demonstrated based on the interlocked geometry of hierarchical polydimethylsiloxane micropillar arrays decorated with ZnO nanowire forests. While the e‐skin in a piezoresistive mode enables a static pressure detection with a high sensitivity, the piezoelectric e‐skin mode permits the dynamic sensing of high frequency vibrations.